Lignans and polyphenols of Phyllanthus amarus schumach and thonn induce apoptosis in HCT116 human colon cancer cells through caspases-dependent pathway - Ibrahim Jantan (Tanjung Malim, 2021)
Lignans and polyphenols of Phyllanthus amarus schumach and thonn induce apoptosis in HCT116 human colon cancer cells through caspases-dependent pathway by Ibrahim Jantan